2017
DOI: 10.1109/tbcas.2016.2547864
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Headstage for Combined Optogenetics and Multichannel Electrophysiological Recording

Abstract: This paper presents a wireless headstage with real-time spike detection and data compression for combined optogenetics and multichannel electrophysiological recording. The proposed headstage, which is intended to perform both optical stimulation and electrophysiological recordings simultaneously in freely moving transgenic rodents, is entirely built with commercial off-the-shelf components, and includes 32 recording channels and 32 optical stimulation channels. It can detect, compress and transmit full action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…Therefore, translating these devices into clinical applications would require further power optimization efforts to avoid battery life and thermal issues. Meanwhile, [10] and our own effort employ optogenetic based stimulations [33], while the others use traditional electrical stimulation, which cannot be genetically targetted [34]. Regarding freely moving experiments, our system also shows both primates/rodents reliable LFP recordings.…”
Section: B the Comparison To The Other Workmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, translating these devices into clinical applications would require further power optimization efforts to avoid battery life and thermal issues. Meanwhile, [10] and our own effort employ optogenetic based stimulations [33], while the others use traditional electrical stimulation, which cannot be genetically targetted [34]. Regarding freely moving experiments, our system also shows both primates/rodents reliable LFP recordings.…”
Section: B the Comparison To The Other Workmentioning
confidence: 94%
“…However, the overall consumption was significantly large at 284mW. Similarly, Gagnon-Turcotte et al demonstrated a strong computing scalability system with 32 recording/stimulation channels with a comprehensive wavelet data compression technique [10]. The power consumption is still relatively high at 119mW.…”
Section: B the Comparison To The Other Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Future modifications of the described hard-and software framework will also accommodate the combination of electrical and optical stimulation (combined oCI and eCI) for hybrid electro-optical stimulation 26 or optofluidics circuitry for application of photopharmacology into the cochlea and later optical stimulation [67][68][69] . Most studies presenting optogenetic stimulators address brain stimulation [70][71][72][73] , e.g. cortical control of movement 74 , and also peripheral nervous system 75 .…”
Section: Utility Of the Developed Oci Systemmentioning
confidence: 99%
“…Existing systems used in research are capable of wirelessly transmitting recorded neural signals [2,4,19,20] and wirelessly controlling stimulation [21], but some systems are limited by the use of noncommercial ASIC designs [2,4,21,22] or do not provide on-board synchronized recording with external stimuli [5,23,24] but this is not without exception [21]. Devices capable of simultaneous surface electrical or optical stimulation and recording have also been developed with low-power consumption and high noise immunity [22,25,26].…”
Section: Introductionmentioning
confidence: 99%